KANDUNGAN PROTEIN, LEMAK DAGING DAN KULIT ITIK, ENTOG DAN MANDALUNG UMUR 8 MINGGU - Andi Pertiwi Damayanti (Universitas Tadulako, 2006)
This experiment was done to determine the chemical composition of meats of duck, Entog, and Mandalung. A proximate analysis of chemical composition was performed on samples obtained from 4 ducks, 3 Entog and 3 Mandalung; all were at 8 moths old. Results indicated that the highest protein content for chest meat was found in the duck (20.04%) followed by mandalung (19.01%) and entog (18.29%); respectively. The highest protein content for husk was obtained in the chest husks of entog (12.9%) followed by drumstick husks of mandalung (12.98%). The fat flesh content of entog, duck and mandalung were 59.32, 38.67, and 68.49%, respectively. The proportions of the husk of drumstick were 52.67, 97.64 and 48.85% for duck, entog and mandalung respectively. The highest chest fat contents was found in the mandalung (5.06%) followed by duck (3.84%) and entog (3.47%). The drumstick husks content was 8.47% for duck, 5.27% for entog, and 11.69% for mandalung. This study clearly indicated that the proportion of fat was high in meat husk of all three species. For this reason, it is suggested for consumers to exclude the husk of these meat products in reducing fat consumption.